Oil Security Short- and Long-Term Policies - Valeria Costantini; Francesco Gracceva (Fondazione Eni Enrico Mattei (FEEM), 2004)
Increasing oil security represents one of the most important policy actions, especially within IEA countries. Short and long term mechanisms could help such goal. On the short term side, revision of IEA emergency response oil stock system has been discussed. The attention is mainly focused on three issues: the high costs of stock management for private industries, the possible use of strategic reserves to smooth price when no high supply disruption has taken, the extension of IEA emergency system to non-OECD countries. The main actions specifically proposed by the European Commission are: an harmonisation of national storage systems, with the institution of public and private agency, a wider co-ordinated use of security stocks, and an increase in the physical amount of oil stocks. Long term measures for enhancing oil supply security can be seen on the demand-side and the supply-side. Main demand-side policies could be the following: energy saving and efficiency, investments in research and technology, and reduction of oil price inelasticity especially for transport sector. Main supply-side policies can be summarized into co-operation and institutional promotion for supply diversification of suppliers/routes. Main factors that could affect described policies could be the liberalization of international trade even in the energy sector and the increasing role of oil demand from developing countries.
Keywords: Q41; Q43; 330; Oil; Security; Energy; Energieversorgung; Erdöl; Erdölpolitik; OECD-Staaten